PENGARUH MODEL SMALL GROUP DISCUSSION (SGD) TERHADAP KEMAMPUAN KOMUNIKASI SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS V SDN PEGADUNGAN 05 PAGI - Agustinauli, Sarima; Ainur Rosyid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the influence of the small group discussion model on students' communication skills in grade V of SDN Pegadungan 05 Pagi. This study is a quantitative research using an experimental method with a type of one group pretest posttest design. The sample in this study is 30 students in class V A. The data collection technique in this study is using questionnaires and pre-test post-test. The results obtained from students in class V A when conducting the pretest before being given the small group discussion model got an average score of 72.82 and after being given the small group discussion model got an average score of 90.73. After obtaining the results, the researcher conducted a hypothesis test to find out if there was an influence of the small group discussion model on the communication skills of students in this study. Based on the t-test with the Paired Sample T-Test, it can be seen that the t-results are calculated 23,642 > t-table 2,045 and the significant value is 0.000 > 0.05. The results showed that H0 was rejected and H1 was accepted, which means that there was an influence of the small group discussion model on the communication skills of students in grade V of SDN Pegadungan 05 Pagi.